Main changes in biopsychosocial aspects of Chilean teenagers after two years of remote emergency teaching - Sánchez-Uribe, Gonzalo; Jaramillo-Arce, Génesis; Quiroga-Sanzana, Claudia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The lockdown during the COVID-19 pandemic was an adjustment process in life for everyone. The aim of this research, framed in the thesis of Social Work of the University of Concepción "Main changes in the biopsychosocial development of teenagers from the commune of Coronel, after two years of remote emergency teaching ", was to explore and describe the changes following emergency remote teaching in biopsychosocial aspects of adolescents. The following variables were analyzed in three dimensions. In the Biological Dimension, physical activity, diet behavior, and sleep quality were measured. The Psychological Dimension addressed feelings of life satisfaction, positive mental well-being, and moods and feelings. Finally, the social dimension assessed social participation.A quantitative methodology was proposed, with a descriptive, relational, and transversal design. The sample was composed of 194 students between 14 and 18 years of age, from five educational establishments of municipal dependence of the commune of Coronel, Biobío region, Chile. For data collection purposes, a self-administered questionnaire was used. The results indicated that the main changes in the lives of adolescents were observed in the areas of physical activity, positive mental well-being, and social participation; in turn, men presented a greater positive mental well-being than women.